Rhodes Framework for Android™ Platform and BlackBerry® Smartphones - Vohra, Deepak (SpringerBriefs in Computer Science, 2012)
The Rhodes framework offers several advantages over other mobile frameworks. Some of the unique features of the Rhodes frameworks are as follows: - The only smartphone framework to offer support for the Model View Controller pattern - The only smartphone framework to offer support for the Object-Relational manager -The only smartphone framework to offer offline, disconnected access to data with the Rho-Synch server - The only smartphone framework to support all mobile devices including Android, BlackBerry, iPhone, Symbian, and Windows - Provides Ruby implementations for all smartphone device operating systems -Provides a web-based Integrated Development Environment for developing mobile applications for all smartphone platforms with the RhoHub development service This book discusses developing Rhodes applications for Android and the BlackBerry platform, as these are the two most commonly used mobile platforms. For each, an application for creating a catalog and another application for getting RSS feed will be developed.  .